HUBUNGAN GAYA MENGAJAR, MOTIVASI BELAJAR DAN POLA ASUH ORANGTUA TERHADAP PRESTASI BELAJAR SISWA SDN KUTISARI I/268 SURABAYA - Mudzakkir, Mudzakkir; El Yunusi, Muhammad Yusron Maulana; Darmawan, Didit (IAIN Bone, 2024)
This study aims to determine the effect of teaching style, learning motivation, and parenting style on student learning achievement at SDN Kutisari I/268 Surabaya. The population and sample in this study were all students in grade VI and part of grade V at SDN Kutisari I/268 Surabaya. Data collection in this study used a questionnaire using a quantitative approach. The analysis techniques used were validity and reliability tests, classical assumption tests, multiple linear regression tests, t tests, f tests, and coefficient of determination tests. The results showed that varied teaching styles, strong learning motivation, and supportive parenting had a significant positive impact on student achievement at SDN Kutisari I268 Surabaya. The results of this study emphasize the importance of the role of teachers, parents, and student motivation in creating an optimal learning environment to improve learning outcomes.Â